812. IRIS SCHELKOWNIKOWII. (June 2015) - Rix, Martyn; Garakhani, Parvana; Selimov, Resad; Strange, Kit
Summary Iris schelkownikowii (Fomin) Fomin, a little‐known species from Azerbaijan in section Oncocyclus, is described and illustrated. Suggestions for its cultivation are given.